Peningkatan Motivasi Kerja dan Kinerja Pegawai Melalui Peran Kepemimpinan, Kompetensi dan Disiplin Kerja pada Kecamatan Kartasura - Lathifah, Ifah; Yuniastuti, Fitri (CV. Kalimasada Group, 2023)
The aim is to find out, test and analyze the role of leadership, competence and work discipline on work motivation and performance of Kartasura District employees. Data collection methods are observation and questionnaires. Census sampling technique as many as 39 respondents. Data analysis includes instrument testing, linearity testing, hypothesis testing, and path analysis. The results of the study prove that work discipline has a significant impact on work motivation, but leadership and competence have an insignificant impact; leadership and competence have a significant impact on performance but work discipline and work motivation have an insignificant impact. The F test proves that leadership, competence, work discipline and work motivation have a significant impact on performance. Total R2 test = 0.852, performance is explained by leadership, competence, work discipline, and work motivation = 85.2% and the remaining 14.8% is explained by other factors. Path analysis proves that the direct path of competence is the most dominant and effective path in increasing performance. Work motivation is not an intervening variable, because it is less effective in mediating the relationship between leadership, competence and work discipline with performance.